Fundamentals of Volunteer Orientation - Olivia Caroline Caillouet; Jessica Williams; Shelby Atwood; Matt Benge (EDIS)
We created this fact sheet to assist volunteer managers when creating volunteer orientations for their new volunteers. Volunteer training and orientation is a critical component which should promote volunteers’ understanding of the role they hold within organizations. Leaders of volunteer organizations must ensure their organizations have adequately prepared volunteers to carry out the organization’s mission. Last, volunteer leaders should incorporate the cause, system, and social orientation components to effectively create an orientation focused on providing the appropriate onboarding of their most valuable asset – volunteers.